Therapeutic Effect of Ultrasound Combined With Porous Lipid Clioquinol/PLGA Microbubbles on Ferroptosis in HL-1 Cardiac Cell Induced by Isoproterenol Attack - Li, Nana; Dong, Lei; Shen, Yuanyuan; Wang, Yongling; Chang, Liansheng; Wu, Hongwei; Chang, Yuqiao; Li, Menghao; Li, Dan; Li, Zhaoyi; He, Mei; Li, Cheng; et al. (Frontiers in Pharmacology, 2022)
Abstract: In recent years, studies have shown a close relationship between cardiomyocyte death and ferroptosis. Clioquinol (CQ) can inhibit ferroptosis. Porous lipid poly(lactic-co-glycolic acid) (PLGA) microbubbles (MBs) were prepared by double emulsification (W1/O/W2) using 1,2-Dioctadecanoyl-sn-glycero-3-phophocholine (DSPC) and PLGA as raw materials. Porous lipid PLGA MBs were used as carriers to prepare CQ/PLGA MBs containing CQ. CQ/PLGA had the advantages of high drug loading, good biocompatibility, and sustained release. Our results showed that CQ/PLGA improved the effect of CQ and reduced its cytotoxicity. Under low-frequency ultrasound with certain parameters, CQ/PLGA showed steady-state cavitation, which increased the membrane permeability of mouse cardiomyocyte HL-1 to a certain extent and further prevented the process of ferroptosis in mouse cardiomyocyte HL-1.